Studying modern drama - Pickering, Kenneth (Palgrave Macmillan, 2003)
There has probably never been a period to compare with the modern age in which there has been such diversity in the forms of drama and the ways in which it is made. Guides you through the entire process of drama study with a careful, step-by-step approach to the task, discusses the characteristics and conventions of modern darma as well as language, and structure and introduces a workshop method of exploring texts and is full of activities and advice to hepl you with criticism and essay-writing.